Comparison of two ERCC1 antibodies as prognostic and predictive biomarkers for early non-small cell lung cancer - Muley, Thomas; Sianidou, Maria; Bischoff, Helge; Schneider, Marc; Warth, Arne (Anticancer research, 2014)
Aim: Expression of excision repair cross-complementing rodent repair deficiency, complementation group 1 (ERCC1) was suggested to be of predictive value for selecting patients with clinical benefit from platinum-based chemotherapy. Patients and Methods: In order to validate the prognostic and predictive value of ERCC1, we comparatively analyzed 298 patients with non-small cell lung cancer (NSCLC) treated with and without platinum-based adjuvant chemotherapy with two different antibodies against ERCC1 (clones 8F1 and SP68). Results: We found that both antibodies have a different immunoreactivity, with SP68 showing a more distinct, predominantly nuclear staining pattern. There was no prognostic effect for patients with high compared to patients with low ERCC1 expression, regardless of the antibody applied. In contrast, patients with squamous cell carcinoma treated with adjuvant platinum-based chemotherapy who had a low ERCC1 expression had a survival benefit with respect to disease-free and overall survival. This was especially true for expression by the SP68 antibody. Conclusion: Oour data point to a potential predictive value of ERCC1 expression for the selection of adjuvant platinum-based chemotherapy for patients with pulmonary squamous cell carcinomas but not for those with adenocarcinomas. With more specific antibodies in hand, this should be substantiated in subsequent clinical studies.